PENGARUH LIKUIDITAS DAN LEVERAGE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2015-2019 - Safrin Maruli Tua (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2021)
The Effect of Liquidity and Leverage on Disclosure of Corporate Social Responsibility in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) 2015-2019 period. The purpose of this study is to determine whether the effect of liquidity on disclosure of corporate social responsibility in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period, to determine whether the effect of leverage on disclosure of corporate social responsibility in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period, to determine whether the effect of liquidity and leverage on the disclosure of corporate social responsibility in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. This type of research is a type of quantitative research. The type of data used in this study is secondary data in the form of corporate financial reports listed on the Indonesia Stock Exchange, such as corporate financial reports and corporate social responsibility. The population in this study were all manufacturing companies listed on company reports on the IDX in 2015,2015,2017,2018 and 2019. The sample in this study was conducted using purposive sampling method, the total sample in this study was 50 data from 10 manufacturing companies listed on the Indonesia Stock Exchange. The data analysis method used multiple linear regression. Liquidity has a positive and significant effect on the disclosure of corporate social responsibility in manufacturing companies listed on the IDX for the 2015-2019 period. This is indicated by a significance level of 0.026 with a regression coefficient of 0.037. leverage has a negatife and significant effect on the disclosure of corporate social responsibility in manufacturing companies listed on the IDX for the 2015-2019 period. Tihis is indicated by a significance level of 0.005 with a regression coefficient of -0.047.